2015
DOI: 10.1128/iai.00032-15
|View full text |Cite
|
Sign up to set email alerts
|

Apparent Role for Borrelia burgdorferi LuxS during Mammalian Infection

Abstract: The Lyme disease spirochete, Borrelia burgdorferi, controls protein expression patterns during its tick-mammal infection cycle. Earlier studies demonstrated that B. burgdorferi synthesizes 4,5-dihydroxy-2,3-pentanedione (autoinducer-2 [AI-2]) and responds to AI-2 by measurably changing production of several infection-associated proteins. luxS mutants, which are unable to produce AI-2, exhibit altered production of several proteins. B. burgdorferi cannot utilize the other product of LuxS, homocysteine, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…As a large competition assay, the Tn‐seq screen may reveal subtle phenotypes missed in traditional single strain infections. A similar phenomenon in mice has been reported for B. burgdorferi lacking luxS (Arnold et al ., ). For many years, it was thought that luxS mutants were fully infectious (Hubner et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…As a large competition assay, the Tn‐seq screen may reveal subtle phenotypes missed in traditional single strain infections. A similar phenomenon in mice has been reported for B. burgdorferi lacking luxS (Arnold et al ., ). For many years, it was thought that luxS mutants were fully infectious (Hubner et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…For many years, it was thought that luxS mutants were fully infectious (Hubner et al, 2003). However, an infectivity defect was uncovered in a recent publication in which luxS mutants were out competed by wild-type during mouse infection (Arnold et al, 2015).…”
Section: In Vivo Fitness Of Mutants With Insertions In the Carbohydramentioning
confidence: 99%
“…One group reported that a luxS-deficient clone of Bb strain 297 retained its infectivity in mice following needle inoculation [232], and also maintained its capacity for tick colonization and transmission [233]. Although the infectivity of the luxS mutant strain was confirmed recently by a quantitative approach that evaluated bacterial burden in tissues, a mixed infection with wildtype and mutant Bb favoured the wildtype cells [234]. This result suggests that LuxS may, indeed, contribute to mammalian colonization, dissemination, and persistence, in ways that are not yet clear.…”
Section: Environmental Challenges and Microbial Adaptationsmentioning
confidence: 99%
“…2) (Pal et al, 2004;Ferullo and Lovett, 2008;Traxler et al, 2008;Dunham-Ems et al, 2009;2012;Srivastava and de Silva, 2009;Zhang et al, 2011;Meril€ ainen et al, 2015;Gupta et al, 2016). It is plausible that the stringent response mediates these processes since the stringent response in B. burgdorferi (like that in other bacteria) modulates expression of genes of the mevalonate pathway involved in cell wall morphogenesis, inhibition of motility, formation of aggregates and biofilms, and quorum sensing (Potrykus and Cashel, 2008;Dalebroux and Swanson, 2012;Boutte and Crosson, 2013;Arnold et al, 2015;Bugrysheva et al, 2015;Drecktrah et al, 2015;Gupta et al, 2016). After 48 h of feeding, as nutrients from the blood meal begin to be utilized by tick gut epithelial cells and increased nutrients are available to the spirochetes, the stringent response will subside, and spirochetes will begin to divide and rapidly reach high concentrations (Piesman et al, 1990;Dunham-Ems et al, 2009).…”
Section: Introductionmentioning
confidence: 99%